Recycling Solid Waste for Sustainable Landscape Applications - Candan Kus Sahin; Busra Onay (Emerging Issues in Environment, Geography and Earth Science Vol. 5, 2023)
Although there are numerous ways to categorize wastes, in simplicity, they could be classified as their main structural elements (i.e., metals, plastics, woods or substances which are made with a combination of materials). In general, the cost of secondary materials is somewhat pricey compared to counterpart virgin materials. In order to compete with these complex challenges, professionals need timely information on innovative projects. As the recycling industry grows, the application of secondary materials (waste materials) in urban open spaces, easily accessible to the public and applying many meanings to the cities, has increased. There are many abandoned materials from municipal and industrial streams that could be used as urban furniture elements that promote sustainable built environment awareness. In that case, significant progress has been made in the past decade involving the enhancement of design practices and the development of cost-effective elements. However, successful urban space design is only possible when professionals have knowledge of materials and their properties during life service. From the perspective of sustainable environmental design, this study discusses the waste of recycling, and, through case study, presents the re-utilization in landscape design of urban furniture elements.